An Assessment of Google Classroom Reception and Usage among Preservice Science, Technology and Mathematics Teachers in South-West Nigeria - Awofala, Adeneye Olarewaju A.; Oladipo, Adenike J.; Akinoso, Sabainah O.; Arigbabu, Abayomi A.; Fatade, Alfred O. (FKIP Universitas Lampung, 2022)
Objectives: The present study assessed google classroom reception and usage among preservice STM teachers in south-west Nigeria. Methods: The participants were 480 preservice STM teachers purposively selected from four universities in south-west Nigeria within the blueprint of a correlational survey research design. Data analysis was carried out using mean, standard deviation, Pearson product moment correlation coefficient and multiple regression analysis at 5% level of significance. Findings: Results showed that 94.1% of the variance in preservice STM teachers’ actual use of google classroom was accounted for by a combination of attitude towards use, perceived ease of use, perceived usefulness, and behavioural intention to use google classroom. Conclusion: Conclusively, STM teachers’ educator should promote the adoption and utilization of google classroom among the preservice STM teachers to increase their reception of google classroom for instructional purposes. Keywords: reception, google classroom, stm, technology acceptance model, preservice teachers.DOI: http://dx.doi.org/10.23960/jpp.v12.i2.202231